2023
DOI: 10.1039/d2cc06146e
|View full text |Cite
|
Sign up to set email alerts
|

Tracking endoplasmic reticulum viscosity during ferroptosis and autophagy using a molecular rotor probe

Abstract: Ferroptosis is a unique non-apoptotic cell death process associated with endoplasmic reticulum (ER) stress-related diseases. We have designed and synthesized a far-red emitting and ER targetable viscosity-sensitive fluorophore to track...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…The endoplasmic reticulum (ER), where CRT is located, plays a crucial role in ICD. , Many small-molecule-based ICD triggers act by causing ER stress and elevating reactive oxygen species (ROS) levels, which is mainly attributed to protein misfolding and lipid accumulation in the ER lumen. These accumulated proteins or lipids may alter the microenvironments of ER, e.g., viscosity. A variety of fluorescent molecular rotors have been developed for the imaging of viscosity in live cells, e.g., molecular rotors based on 9-(2-carboxy-2-cyanovinyl)­julolidine (CCVJ) and 4,4-difluoro-boradiazaindacene (BODIPY) with a rotatable moiety have been developed as cellular viscosity mapping probes with specific organelle targeting properties in living cells. , …”
Section: Introductionmentioning
confidence: 99%
“…The endoplasmic reticulum (ER), where CRT is located, plays a crucial role in ICD. , Many small-molecule-based ICD triggers act by causing ER stress and elevating reactive oxygen species (ROS) levels, which is mainly attributed to protein misfolding and lipid accumulation in the ER lumen. These accumulated proteins or lipids may alter the microenvironments of ER, e.g., viscosity. A variety of fluorescent molecular rotors have been developed for the imaging of viscosity in live cells, e.g., molecular rotors based on 9-(2-carboxy-2-cyanovinyl)­julolidine (CCVJ) and 4,4-difluoro-boradiazaindacene (BODIPY) with a rotatable moiety have been developed as cellular viscosity mapping probes with specific organelle targeting properties in living cells. , …”
Section: Introductionmentioning
confidence: 99%
“…The probe of interest has julolidine as donor and dicyano as the acceptor, which are connected through an extended conjugation to provide far-red emission. 44,45 The acceptor part has been incorporated with the 3-indole group to enhance the probe sensitivity towards viscosity. Compound 1 was synthesized as previously reported that was sensitive to viscosity.…”
Section: Design and Synthesismentioning
confidence: 99%
“…When ER stress occurs, misfolded and unfolded proteins accumulate in the ER, leading to an elevation in ER viscosity. 39 A list of julolidine-based far-red emissive FMRs used for understanding sub-cellular organelle viscosity under stress conditions is provided in Fig. 14.…”
Section: Viscosity Sensing Of the Microenvironmentmentioning
confidence: 99%